2017
DOI: 10.5334/tohm.338
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Suffering in Essential Tremor: A Study of Patients and Those Who Are Close to Them

Abstract: Background: Although the motor and non-motor features of essential tremor (ET) have been characterized in detail, it is not known whether ET patients suffer psychologically and whether those who are close to them consider them to be suffering in this way. Methods: Fifty ET patients and 50 ''close others'' (COs), identified by patients ''as someone who knows you well and sees you often'' and who can ''provide a different perspective on your well-being'', reported their own depressive symptoms, daily stress, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Open-ended questions were designed based on aspects of the ET caregiving relationship that may have particular importance based on previous findings. Previous studies have found that those with ET experience embarrassment at high rates and that ET caregivers experience increased burden when they perceive more embarrassment in care-recipients and that they experience increased depression when they perceive more suffering (Kellner et al, 2017;Monin et al, 2017). This, combined with the significant public component of embarrassment, guided our focus on caregiving situations both in public and private that may cause strain or distress for both the caregiver and care-recipient.…”
Section: Survey Development and Distributionmentioning
confidence: 93%
See 1 more Smart Citation
“…Open-ended questions were designed based on aspects of the ET caregiving relationship that may have particular importance based on previous findings. Previous studies have found that those with ET experience embarrassment at high rates and that ET caregivers experience increased burden when they perceive more embarrassment in care-recipients and that they experience increased depression when they perceive more suffering (Kellner et al, 2017;Monin et al, 2017). This, combined with the significant public component of embarrassment, guided our focus on caregiving situations both in public and private that may cause strain or distress for both the caregiver and care-recipient.…”
Section: Survey Development and Distributionmentioning
confidence: 93%
“…Tasks that require assistance in public, such as completing forms or eating, could result in heightened embarrassment for the individual with ET. Recent research also shows that caregivers' perception of their care-recipient's embarrassment is associated with increased caregiver burden (Kellner et al, 2017;Monin et al, 2017;Morgan et al, 2017). Another study showed that caregivers' perceptions of suffering in their care-recipients was associated with caregiver depression (Monin et al, 2017;Morgan et al, 2017).…”
mentioning
confidence: 99%
“…The Clinical Pathological Study of Cognitive Impairment in Essential Tremor (COGNET), a longitudinal study that evaluates cognitive function in older adults with ET, reported that both patients with ET and those close to them suffer psychological stress [ 13 ]. In addition, patients may develop feelings of social isolation [ 11 , 14 ] and depression [ 6 , 11 , 13 ]. Due to the incredible burden put on individuals diagnosed with ET or PD, a multitude of approaches have been investigated to improve the symptoms and quality of life of those afflicted.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most common movement disorders, especially in the elderlys (Louis and Ferreira, 2010;Sepúlveda Soto and Fasano, 2020), and a potential risk factor for other neuropsychiatric conditions, such as depression and anxiety (Huang et al, 2019;Louis, 2010). The socio-economic burden inflicted by ET is insurmountable, as it negatively affects the well-being and productivity of the patients and their caregivers (Monin et al, 2017). Current therapeutic agents for ET are limited and often hampered by either inadequate efficacy or intolerable side effects (Shanker, 2019).…”
Section: Introductionmentioning
confidence: 99%